2019
DOI: 10.1002/jcb.29115
|View full text |Cite
|
Sign up to set email alerts
|

Joint detection of claudin‐1 and junctional adhesion molecule‐A as a therapeutic target in oral epithelial dysplasia and oral squamous cell carcinoma

Abstract: Abnormal expression of claudin‐1 (CLDN‐1) and junctional adhesion molecule‐A (JAM‐A) has been described in certain malignancies but their clinical relevance is poorly understood. The present study aims to elucidate the role of CLDN‐1 and JAM‐A in oral epithelial dysplasia (OED) and oral squamous cell carcinoma (OSCC). Changes in the expression of these proteins were identified immunohistochemically on tissue sections from patients with OED and OSCC and compared with control. A correlation between the expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 55 publications
0
23
1
Order By: Relevance
“…Collective migration is observed in many aggressive cancers in which a group of cells maintain a coordinated movement guided by the cues from the microenvironment (Yang et al, 2019b). Contrary to the migratory single cells that exhibit complete loss of cell-cell adhesion, migratory cell clusters preserve cell-cell junctions principally through ECAD (Singh et al, 2016(Singh et al, , 2019, gap junctions (Citi et al, 2014;Kuznik et al, 2016;Park et al, 2016;Leech et al, 2018;Upadhaya et al, 2019;Zhang et al, 2020), and surface adherent proteins from the immunoglobulin family (Friedl et al, 2012;Aiello et al, 2018).…”
Section: Pemt and Collective Migrationmentioning
confidence: 99%
“…Collective migration is observed in many aggressive cancers in which a group of cells maintain a coordinated movement guided by the cues from the microenvironment (Yang et al, 2019b). Contrary to the migratory single cells that exhibit complete loss of cell-cell adhesion, migratory cell clusters preserve cell-cell junctions principally through ECAD (Singh et al, 2016(Singh et al, , 2019, gap junctions (Citi et al, 2014;Kuznik et al, 2016;Park et al, 2016;Leech et al, 2018;Upadhaya et al, 2019;Zhang et al, 2020), and surface adherent proteins from the immunoglobulin family (Friedl et al, 2012;Aiello et al, 2018).…”
Section: Pemt and Collective Migrationmentioning
confidence: 99%
“…Numerous studies reported that claudin-1 play a significant role in this type of cancer and its elevated expression is observed in most oral, carcinomas. Moreover, the higher the expression, the more advanced stage tumors are diagnosed, and what is worth emphasizing-it is also associated with a lower survival rate [54][55][56][57]. Patricia Pintor Dos Reis et al showed that overexpression of CLDN1 is associated with higher invasion of cells and aggressiveness observed in immunohistochemistry [58].…”
Section: Oral Cancermentioning
confidence: 99%
“…Recently, the F11R/JAM-A protein expression was investigated by Upadhaya et al [ 127 ] in oral epithelial dysplasia (OED) and oral squamous cell carcinoma (OSCC). Revealed F11R/JAM-A overexpression was related to cancer cell perineural invasion, aggressive histological tumor grades, and correlated with a low survival rate in comparison to cancer patients with F11R/JAM-A underexpression.…”
Section: F11r/jam-a Expression In Cancermentioning
confidence: 99%
“…The authors suggested that the dimerization mechanism is responsible for the high F11R/JAM-A level. In most OSCC tissues, F11R/JAM-A was delocalized to the cytoplasm from the cell membrane [ 127 ].…”
Section: F11r/jam-a Expression In Cancermentioning
confidence: 99%